Luigi Valadier - González-Palacios, Alvar 1936- (The Frick Collection, 2018)
Of the many artists who flourished in Rome during the eighteenth century, the silversmith Luigi Valadier (1726-1785) was particularly admired by popes, royalty, and aristocrats across Europe. Luigi Valadier: Splendor in Eighteenth-Century Rome, co-curated by Alvar González-Palacios and Xavier F. Salomon, will bring together more than sixty extradordinary works by the renowned silversmith in celebration of his unsurpassed technical expertise and avant-garde aesthetic